Beam Size Design for LEO Satellite Networks with Doppler Shift Characteristics - Han, Sangmin; Shin, Wonjae; Kim, Jae Hyun (International Conference on ICT Convergence, 2022)
Low Earth Orbit (LEO) satellite networks need to consider the high mobility of LEO satellites. The high Doppler shift due to the mobility of LEO satellites occurs essentially and its scale is not considered in the terrestrial network. Therefore, it is difficult to overcome the Doppler shift in LEO satellite networks with the existing terrestrial network design. In this paper, we propose a LEO sate0llite beam design considering Doppler shift. After calculating Doppler shift and compensation, we analyze the characteristics of Doppler shift in LEO satellite networks. Given OFDM numerology technology of 5G NR (New Radio) and carrier frequency, the LEO satellite beam size is determined differently.
Keywords: Bbeam size; Beam size; High mobility; Low earth orbit satellite network; Low earth orbit satellites; Network design; OFDM numerology; Pre-compensation; Satellite network; Terrestrial networks; bBeam size; Doppler shift; Low Earth Orbit (LEO) satellite networks; OFDM numerology; pre-compensation